2007
DOI: 10.1073/pnas.0701809104
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for streptogramin B resistance in Staphylococcus aureus by virginiamycin B lyase

Abstract: The streptogramin combination therapy of quinupristin-dalfopristin (Synercid) is used to treat infections caused by bacterial pathogens, such as methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus faecium. However, the effectiveness of this therapy is being compromised because of an increased incidence of streptogramin resistance. One of the clinically observed mechanisms of resistance is enzymatic inactivation of the type B streptogramins, such as quinupristin, by a streptogramin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 36 publications
(42 reference statements)
8
42
2
Order By: Relevance
“…genes 3580 to 3583 and 4225/4226 in contigs 35 and 43, respectively) through the induction of modifications in the LPS structure that results in reduced binding to polymyxins (Olaitan et al, 2014). Finally, a gene coding for a Virginiamycin B lyase, an enzyme responsible for the inactivation of type B streptogramin antibiotics (Korczynska et al, 2007), was identified (gene 4095 in contig 42). Additionally, a gene coding for a putative vancomycin B-type resistance protein was identified, which displayed 32.3% similarity with a gene present in a VanG type vancomycin resistance operon characteristic of Enterococcus and Eubacterium (Boyd et al, 2006;Courvalin, 2006).…”
Section: Resistance Genetic Determinantsmentioning
confidence: 97%
“…genes 3580 to 3583 and 4225/4226 in contigs 35 and 43, respectively) through the induction of modifications in the LPS structure that results in reduced binding to polymyxins (Olaitan et al, 2014). Finally, a gene coding for a Virginiamycin B lyase, an enzyme responsible for the inactivation of type B streptogramin antibiotics (Korczynska et al, 2007), was identified (gene 4095 in contig 42). Additionally, a gene coding for a putative vancomycin B-type resistance protein was identified, which displayed 32.3% similarity with a gene present in a VanG type vancomycin resistance operon characteristic of Enterococcus and Eubacterium (Boyd et al, 2006;Courvalin, 2006).…”
Section: Resistance Genetic Determinantsmentioning
confidence: 97%
“…One possibility is that it is a remnant of the use of activated Glu for other chemistry by the ancestors of LanB proteins. Although unexpected in the context of Ser and Thr dehydration, the elimination of a carboxylate from an ester linkage to the side chain of Thr in peptides has precedent in the resistance protein to the cyclic hexadepsipeptide virginiamycin (30,31) as well as related streptogramin antibiotics (32,33). The virginiamycin B lyase (Vgb) from Staphylococcus aureus catalyzes an elimination reaction of the macrolactone that is formed by an ester bond between the hydroxy group of a Thr and the Cterminal carboylic acid (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…106 Enzymatic cleavage of the ring structure of quinupristin by the lactonases VgbA and VgbB, originally described in staphylococci, leads to inactivation of the compound. 107 The ermB gene involved in macrolide resistance is a ribosomal methyltransferase, which also affects the binding of quinupristin. It confers a phenotype, MLS B (for Macrolide, Lincosamide, Streptogramin B), that results in resistance to these antibiotics and is widespread in enterococci.…”
Section: Streptograminsmentioning
confidence: 99%